(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A radio D-distance in harmonic mean labelling of a connect graph G is an injective map f from the vertex set V(G) to the N such that for two distinct vertices u and v of G, d^D (u,v)+⌈(2f(u)f(v))/(f(u)+f(v))⌉≥〖diam〗^D (G)+1. The radio D-distance harmonic mean number of f,rh^D n(f) is the maximum number assigned to any vertex of G On Radio D-distance harmonic mean number of quadrilateral snake graph and doublequaderilateral snake graph.